Fetomaternal Outcome of Pregnancy in Women with Gestational Diabetes Mellitus - Imtiaz, Hira; Khan, Urva; Fatima Tu Zohra; Shagufta (Indus Journal of Bioscience Research, 2025)
Introduction: Gestational diabetes mellitus (GDM) is associated with increased maternal and fetal complications. This study aimed to evaluate the fetomaternal outcomes in women with GDM, considering glycemic control as a key factor. Methodology: A case series at Gulab Devi Hospital’s Obstetrics and Gynecology Department in Lahore for six months involved 82 pregnant women with GDM, selected through non-probability consecutive sampling. Maternal and fetal outcomes, including pre-eclampsia, cesarean delivery, preterm birth, and neonatal hypoglycemia, were documented. Research utilized SPSS version 20 for data analysis, with Chi-square tests to determine associations (p≤0.05 significance threshold). Results: Among the participants, pre-eclampsia occurred in 24.4%, polyhydramnios in 47.6%, cesarean delivery in 68.3%, and postpartum hemorrhage in 6.1%. Preterm birth was noted in 22.0%, neonatal hypoglycemia in 20.7%, macrosomia in 14.6%, and NICU admission in 40.2%. Conclusion: GDM is linked to high rates of maternal and fetal complications, with neonatal hypoglycemia and congenital anomalies significantly associated with poor glycemic control. Strict monitoring and management of blood glucose levels are essential to improving pregnancy outcomes.